Menyelami Wawasan Buddhayana dalam Kehidupan Masyarakat Modern: Transformasi dan Tantangan - lestari, widya; Sutiyono, Sutiyono; Kasrah, Rini; Kundana, Dedi; Seneru, Wistina (Kajian dan Reviu Jinarakkhita: Jurnal Gerakan Semangat Buddhayana (Jinarakkhita Review & Studies: Journal of Buddhayana Spirit Movement), 2024)
This research explores Buddhist values as a Buddhistic heritage that highlights inclusiveism, pluralism, and universalism, as well as beliefs in dharmakaya, in response to the challenges of modern times. The research method used is qualitative by adopting a library study approach, by collecting primary and secondary information from various sources such as books, articles, and the Internet. Analysis suggests that acceptance of Buddhist values can provide significant benefits to individuals and contemporary societies, including improved spiritual and emotional well-being. Practices of compassion, social harmony, and simplicity in everyday life are thought to strengthen human relationships and shape more sustainable societies. The promotion of Buddhist values is seen as becoming increasingly important in building a more powerful, harmonious, and cultural society.